After Cologne: male circumcision and the law. Parental right, religious liberty or criminal assault?. Issue 7 (22nd May 2013) - Merkel, Reinhard; Putzke, Holm
Abstract : Non-therapeutic circumcision violates boys' right to bodily integrity as well as to self-determination. There is neither any verifiable medical advantage connected with the intervention nor is it painless nor without significant risks. Possible negative consequences for the psychosexual development of circumcised boys (due to substantial loss of highly erogenous tissue) have not yet been sufficiently explored, but appear to ensue in a significant number of cases. According to standard legal criteria, these considerations would normally entail that the operation be deemed an 'impermissible risk'—neither justifiable on grounds of parental rights nor of religious liberty: as with any other freedom right, these end where another person's body begins. Nevertheless, after a resounding decision by a Cologne district court that non-therapeutic circumcision constitutes bodily assault, the German legislature responded by enacting a new statute expressly designed to permit male circumcision even outside of medical settings. We first criticise the normative foundations upon which such a legal concession seems to rest, and then analyse two major flaws in the new German law which we consider emblematic of the difficulty that any legal attempt to protect medically irrelevant genital cutting is bound to face.